Comparison Between Balloon Angioplasty and Surgical treatment for Native Coarctation of the Aorta in Infants - Truba, Y.; Dzuriy, I.; Diachenko, V.; Plyska, O.; Imanov, E.; Lazoryshynetz, V. (Ukrainian Journal of Cardiovascular Surgery, 2018)
Coarctation of the aorta (CoA) is a discrete stenosis of the proximal thoracic aorta. The common clinical pattern is congestive heart failure in infancy. Treatment methods include balloon angioplasty (BA) and surgical repair in this age group. Percutaneous balloon angioplasty is a less invasive method for the repair of discrete coarctation but remains controversial as a primary treatment strategy for a native coarctation. This study aimed to compare the effectiveness and outcome of balloon angioplasty and surgical repair in infants with coarctation of the aorta younger than one year old. Methods. Between January 2011 and December 2017, 59 patients with native aortic coarctation were treated in National Amosov Institute of Cardiovascular Surgery. This retrospective study evaluated the results of the two methods in patients younger than one year old with the diagnosis of coarctation of the aorta. Group 1 included 18 patients who accepted balloon dilatation for discrete coarctation. Group 2 included 41 patients who underwent surgical resection with end-to-end anastomosis. Patients with complex cardiac anomalies were not included in this study. Results. Immediate results revealed no significant difference in the effectiveness of the two methods (p value =0.06). While the rate of recurrent coarctation was significantly lower in the surgery group [1 (2,4%) vs. 13 (72,2%), p value =0.0017]. The mean hospital stay was 6.4±3.6 days in the balloon angioplasty group and 21.5±8.7 days in the surgery group, which constitutes a significant statistical difference (p value <0.05). Aneurysm formation was not encountered. Conclusion. Both surgical repair and balloon angioplasty for native coarctation of the aorta in infants were effective and beneficial. These data suggest that balloon angioplasty can be acceptable alternative to surgical treatment but due to the high level of recoarctation this method may be considered in critically ill infants with congestive heart failure as a primary palliative procedure. The limitations of this study were its retrospective, nonrandomized nature, and smaller case numbers.